PENGARUH EDUKASI PEMBERIAN MAKAN BALITA BERBASIS MEDIA SOSIAL TIKTOK TERHADAP POLA KONSUMSI BALITA DI WILAYAH KERJA PUSKESMAS TANJUNG PINANG - M.Rafif Wijdan; Silvia Mawarti Perdana; Kasyani; Puspita Sari (STKIP Subang, 2026)
Underweight in toddlers remains a nutritional problem in Indonesia, including in the working area of Tanjung Pinang Public Health Center, Jambi City. One factor affecting toddlers’ nutritional status is dietary patterns influenced by parents’ knowledge regarding toddler feeding practices. The use of TikTok social media as a health education platform has considerable potential to improve parents’ knowledge and behavior related to toddler feeding. This study aimed to determine the effect of TikTok-based toddler feeding education on toddlers’ dietary patterns in the working area of Tanjung Pinang Public Health Center. This study used a quasi-experimental design with a two-group pretest-posttest approach. The sample consisted of 57 respondents selected using purposive sampling technique. The intervention group received educational videos through TikTok, while the control group received leaflet media. Dietary patterns were measured using the 24-Hour Food Recall instrument before and after the intervention. Data were analyzed using Paired Sample t-test and Independent Sample t-test. The results showed an improvement in toddlers’ dietary patterns in the intervention group, indicated by increased intake of calories, protein, fat, and carbohydrates after the educational intervention. TikTok-based education had an effect on toddlers’ dietary patterns and can be utilized as an effective health education medium for parents.